Temporal changes in HIV-related stigma and sexual behaviours: An examination of 22 African countries - Danielle Denardo; David A. Cort (Taylor & Francis Group, 2024)
Despite non-trivial success against the HIV epidemic, health experts in Sub-Saharan Africa (SSA) remain concerned about new infections, stigma attitudes, and increasing rates of higher-risk sexual behaviours (HRSBs). Although this concern has produced voluminous scholarship on the behavioural consequences of belonging to stigmatised populations, scholars have only recently examined the behavioural consequences of holding stigmatising attitudes. Existing work generally finds a positive relationship between stigmatising beliefs and the practice of HRSBs. Yet, it is unknown whether this relationship has changed for countries over the past two decades. We fill this gap using Demographic and Health Survey data from 22 SSA countries. We first find that in most countries, the practice of HRSBs has increased, while stigma beliefs have become more tolerant. Second, the relationship between stigma beliefs and HRSBs changed in only six countries: Nigeria, Kenya, Mozambique, Sierra Leone, Ethiopia, and Lesotho. It changed from non-existent or negative to positive in Nigeria, Kenya, Mozambique, and Ethiopia, but non-existent to negative in Sierra Leone. In Lesotho, the positive association weakened over time. These findings highlight the importance of social and epidemic contexts when considering how stigma impacts sexual behaviours and HIV rates in SSA.